Development of MgZn-Based ferrite materials for deflection yokes - Thor, Soo Fung (2000)
Ferrite materials in the form of the deflection yokes constitute a very significant portion of the entire world production of soft ferrites. The main applications are in TV sets and computer display monitors. Thus, this work was initiated to develop soft ferrite materials of the MgZn type suitable for use as deflection yoke materials. As cost plays a very important role in production, the initial part of the project was to develop the required material by manipulating the composition through production grade raw material. Various additives such as CaO, CuO, TiO₂ and La₂O₃ were added to assist in attaining the required properties. Green compacts with a sintering temperature of 1150°C and only air atmosphere were needed to achieve the magnetic and electrical properties close to those of SAMHWA's YL-5 material. A compositional design technique capable of producing deflection yokes material was successfully developed to cater for the television and computer industry in Malaysia.